2020
DOI: 10.1002/mds.28044
|View full text |Cite
|
Sign up to set email alerts
|

Structural Correlates of the Sensorimotor Cerebellum in Parkinson's Disease and Essential Tremor

Abstract: BackgroundParkinson's disease (PD) and essential tremor (ET) are commonly encountered movement disorders. Pathophysiologic processes that localize to the cerebellum are described in both. There are limited studies investigating cerebellar structural changes in these conditions, largely because of inherent challenges in the efficiency of segmentation.MethodsWe applied a novel multiatlas cerebellar segmentation method to T1‐weighted images in 282 PD and 111 essential tremor patients to define 26 cerebellar lobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
5
20
2
Order By: Relevance
“…First, it is interesting to note that differences in the vermis can explain symptomatic differences since it has been shown that such structures mediate gait and balance (Baumann, 2012;Stoodley et al, 2012). Secondly, the differences found in lobules VI and VIII are in line with studies indicating that these lobules perform sensorimotor functions in the cerebellum (Lopez et al, 2020;Lewis et al, 2007;Sharifi et al, 2014;Benninger et al, 2009).…”
Section: Physiopathologysupporting
confidence: 62%
See 3 more Smart Citations
“…First, it is interesting to note that differences in the vermis can explain symptomatic differences since it has been shown that such structures mediate gait and balance (Baumann, 2012;Stoodley et al, 2012). Secondly, the differences found in lobules VI and VIII are in line with studies indicating that these lobules perform sensorimotor functions in the cerebellum (Lopez et al, 2020;Lewis et al, 2007;Sharifi et al, 2014;Benninger et al, 2009).…”
Section: Physiopathologysupporting
confidence: 62%
“…We assessed structural features at both a region-wise and voxel-wise level using two methods: i) MRI intensity using a classical VBM framework, and ii) a texture-based similarity method. We hypothesized that these analyses would provide complimentary results allowing for an assessment of the methodologic tradeoffs, as well as extend previous analyses that employed cerebellar volumetric assessments (Lopez et al, 2020), and VBM comparisons (Lin et al, 2013). We further hypothesized that a texture-based approach would provide greater sensitivity to group differences since this approach may alleviate limitations of volumetric and VBM studies.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Third, cerebellum networks were left out in the model. Although the key molecular events that provoke PD have not been fully understood and the underlying mechanisms involving cerebellum were relatively less reported, considerable evidence has indicated that cerebellum plays an important role in sensorimotor dysregulation and has now received growing attention (Lopez et al, 2020;Maas et al, 2020). For future studies, we will include the cerebellum, and increase our sample size in order to obtain different subgroups based on disease stages.…”
Section: Discussionmentioning
confidence: 99%